ON NON-TYPICAL SOLUTIONS TO TYPICAL PROBLEMS IN PHYSICS - Sargsyan, S.; Manukyan, V.; Nikoghosyan, G. (SUSh Scientific Proceedings, 2025)
This work is devoted to the presentation of the possibility of solving typical problems of the physics course in a non-standard version, as well as to highlighting the usefulness and importance of such an approach. The work refers to the classification of physics problems and methods of their solution according to standard and non-standard types. The idea is put forward that although non-standard or non-typical approaches require only elective problems, it is also desirable to get acquainted with such approaches during the performance of standard educational tasks. This increases students' interest in the subject and stimulates their creative abilities. The article presents examples of tasks, the solutions of which are accompanied by methodological instructions. By analyzing three typical problems, it is shown that in addition to the main, accepted and widespread method of solution, non-standard effective solutions can also be proposed, which is the scientific-methodological novelty of this work. The two tasks considered are standard school physics problems. It is noteworthy that the non-standard method of solving the first problem allows the same approach to be used to solve a more general problem, which is not possible by using the standard method. The third problem is a typical problem for a university physics course, but if a non-standard approach is used, it can also be solved within the framework of school physics knowledge.